å¤åŠ¡æ‹‰é›…å›½ç«‹é«˜ä¸å››æ ¡äºŒå¹´çº§å¦ç”Ÿä½¿ç”¨ä»‹è¯â€œåœ¨â€çš„å›°éš¾åˆ†æž - Maulini, Nur; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractPreposition is one of the part of speech in Mandarin language. There are many preposition existed and some students are misused the "zai" preposition. The cause is because there is difference between the use of "zai" preposition in Bahasa and Mandarin language. To get the information of students' difficulty in using "zai" preposition, researcher choose the grade XI students of SMAN 4 Sungai Raya as the object of research. The result shows that from four ways to use "zai" preposition, they can use it only 42.75 %. Most of students misuse how to insert "zai" preposition in sentence. They tend to insert "zai" preposition after verbs. From this description, the researcher conclude that students are not mastering the rule of how to use "zai" preposition correctly. Keyword : vocabulary, preposition, zai